Synthesis, Characterization, Electrochemistry and Antimicrobial Activity of Zinc(II) Complexes of some Hydrazone Schiff Bases - M. Ali, Hapipah; P, Subramaniam; Basirun W, Jefri; S. M, Zain; Abdullah, Noorlidah; H.L, Teoh; P.M. Nazri, Loqman; Syed Omar, Sharifah Rohaiza (Malaysian Journal of Science, 2006)
A series of hydrazone Schiff bases and their zinc(II) complexes have been synthesized, characterized and evaluated for antimicrobial activity. The new zinc(II) complexes have been prepared in ethanol media by a template condensation of hydrazides, with either ketone or aldehyde and zinc(II) acetate in the presence of triethylamine. The IR, ¹H and ¹³C NMR data indicate that the hydrazone ligands are coordinated to zinc metal. The cyclic voltammetry of these zinc complexes exhibited irreversible oxidation peaks. The electro-oxidation of Zn₂(Clhaptch)₂(py)₂ displayed a diffusion-controlled one electron transfer reaction process. The anti-microbial activity of the ligands and complexes were evaluated by plate diffusion method against some gram-positive bacteria, gram-negative bacteria and two fungi. There was growth inhibition exhibited by ligands and zinc(II) complexes against tested bacteria and fungi.